The relationship between recall of recently versus remotely encoded famous faces and amyloidosis in clinically normal older adults. Issue 1 (23rd November 2017) - Orlovsky, Irina; Huijbers, Willem; Hanseeuw, Bernard J.; Mormino, Elizabeth C.; Hedden, Trey; Buckley, Rachel F.; LaPoint, Molly; Rabin, Jennifer S.; Rentz, Dorene M.; Johnson, Keith A.; Sperling, Reisa A.; Papp, Kathryn V.
Abstract: Introduction: Alzheimer's disease (AD) patients exhibit temporally graded memory loss with remote memories remaining more intact than recent memories. It is unclear whether this temporal pattern is observable in clinically normal adults with amyloid pathology (i.e. preclinical AD). Methods: Participants were asked to recall the names of famous figures most prominent recently (famous after 1990) and remotely (famous from 1960–1980) and were provided with a phonemic cue to ensure that memory failure was not purely due to verbal retrieval weaknesses. In addition, participants identified line drawings of objects. Clinically normal older adults (n = 125) were identified as amyloid β positive or negative (Aβ+/−) using Pittsburgh compound B positron emission tomography. The relationship between Aβ+/− and recall of remote and recent famous face‐names and objects was examined using repeated measures analyses and general linear models controlling for demographics and media usage. Results: When provided with a phonemic cue, Aβ+ participants recalled the names of fewer recent famous faces compared with Aβ− participants. However, recall of remote famous face‐names and objects did not differ by Aβ group. Discussion: Relative sparing of remotely learned information compared with recently learned information is (1) detectable in the preclinical stages of AD and (2) related to amyloid pathology. Both this temporal gradient and assessment of person‐centered rather than object‐centered semantic information may be particularly meaningful for tracking early memory changes in the AD trajectory.